Mesh choice in inguinal hernia repair: key evidence and practical considerations - León-Madrigal, Eduardo; Barragán-Ortega, Jeffrey; Ruiz-Ruiz, Diego; Godínez-Lazarini, Emilio; Tamayo-Gómez, Manuel E.; Sandoval-Polito, Alfonso; De Hoyos-Riebeling, Miguel; A. De Luna-Vega, Dalia; Navalón-Calzada, Andrea; Marquez-Moreno, Juan H.; Gonzalez-Martinez, Aline; Robles-Rojas, Camila; et al. (International Surgery Journal, 2026)
Inguinal hernia repair is one of the most commonly performed procedures in general surgery, with prosthetic mesh reinforcement widely recognized as the standard of care due to its ability to significantly reduce recurrence rates. However, the increasing diversity of available mesh products has introduced important considerations regarding optimal prosthetic selection. Beyond structural reinforcement, mesh characteristics have been shown to influence postoperative pain, foreign body sensation, functional recovery, and overall patient quality of life. This focused review summarizes key evidence surrounding mesh selection in contemporary inguinal hernia repair, emphasizing practical considerations relevant to daily surgical practice. Core variables analyzed include mesh weight, pore size, density, anatomical placement, and fixation strategies. Lightweight meshes have demonstrated favorable outcomes in terms of reduced chronic postoperative pain and improved abdominal wall flexibility, while maintaining acceptable recurrence rates in most primary repairs. Similarly, large-pore and low-density meshes appear to enhance tissue integration and reduce fibrotic response compared with microporous prostheses. Mesh positioning within anterior or posterior planes, as well as the choice between penetrating and atraumatic fixation methods, further influences postoperative outcomes. Techniques such as glue fixation or non-fixation in selected laparoscopic repairs may reduce pain without compromising stability. Ultimately, no single mesh type is universally superior. Prosthetic selection should be individualized based on patient characteristics, hernia complexity, surgical approach, and surgeon expertise. Continued innovation in biomaterials and fixation technologies, alongside standardized outcome reporting, will be essential to refine evidence-based mesh selection and optimize long-term results in inguinal hernia surgery.